PENGARUH PENGALAMAN MEMBELI PRODUK FASHION TERHADAP NIAT MEMBELI KEMBALI MELALUI KEPUASAN DAN KEPERCAYAAN PELANGGAN - Ni Putu Widantari Suandana; Ketut Rahyuda; Ni Nyoman Kerti Yasa (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2016)
repurchase intention through customer satisfaction and trust. Data obtained through questionnaires to 100respondents through purposive sampling for Internet users in Denpasar who have ever bought fashion productsthrough online at least twice in six months. The analysis technique used in this study is the Partial LeastSquare and for intervening variables using Sobel test and effect size. The result of this research shows thatonline fashion buying experience significantly and positively influence the online repurchase intention. Thecustomer satisfaction and trust also significantly and positively influence online repurchase intention. Thecustomer satisfaction also influences their trust positively and significantly. The customer satisfaction andtrust emerges as mediating variable of the influence of online fashion product buying experience on onlinerepurchase intention.